2013
DOI: 10.1353/eas.2013.0003
|View full text |Cite
|
Sign up to set email alerts
|

The Panacea and Perfidy of Cultural Rites of Circumcision in African Countries: Examples From Kenya, Botswana and South Africa

Abstract: Cultural rites can be a panacea when the immense social capital embedded in them is taken stock of as well as they can be a perfidy when all the retrogressive aspects they constitute are taken into consideration. The aim and objective of this article is to generate debate and discourse on panacea and perfidy of cultural rites with particular focus on circumcision. The article used eclectic data sources. Cultural rite of circumcision is a panacea due to an array of factors: it marks entry into adulthood from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…In early this year, 2013, Police and officers from the Provincial Administration in Kilifi County of Kenya revealed that at least 20 individuals suspected of engaging in witchcraft get killed every month (Masha 2013). Although such deaths takes away their cultural rights as well as their human rights embedded in many countries' bill of rights (Barrett-Grant, Fine, Heywood & Strode, 2001;Kang'ethe, 2013), this shows societal change in goal posts towards the place and value of these practitioners.…”
Section: Negatively Perceived Roles Of Healers Sangomas Wizards Andmentioning
confidence: 99%
“…In early this year, 2013, Police and officers from the Provincial Administration in Kilifi County of Kenya revealed that at least 20 individuals suspected of engaging in witchcraft get killed every month (Masha 2013). Although such deaths takes away their cultural rights as well as their human rights embedded in many countries' bill of rights (Barrett-Grant, Fine, Heywood & Strode, 2001;Kang'ethe, 2013), this shows societal change in goal posts towards the place and value of these practitioners.…”
Section: Negatively Perceived Roles Of Healers Sangomas Wizards Andmentioning
confidence: 99%
“…This phenomenon has a cultural dimension in that cultural factors undermine the process of attending and staying in school for a longer time. This is especially common in countries where some traditional communities believe in the girl children being an economic source of livelihood through dowry payment (Alderman & King, 1998;Kang'ethe, 2013b).…”
Section: Social Work Facilitating To Close Gender Parity Gapmentioning
confidence: 99%
“…Having girls not access education as the boys has serious implications in development. This is because girls and therefore women are likely to lag behind men as far as development issues are concerned (Kang'ethe 2013b). This would make it hard for them to attain the much desired gender equality and equity.…”
Section: Social Work Facilitating To Close Gender Parity Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…These are aspects of underdevelopment and constitutes retrogressive aspects of cultures that need to be annihilated altogether (Kang'ethe, 2014C). The parents of such girls therefore, view their girl children as agents of wealth creation (Kang'ethe, 2013b). The environment of marrying people one never knew or choose also presents a fertile ground for gender based violence and the girl may easily be a victim HIV/AIDS (Kang'ethe, 2009(Kang'ethe, , 2014b.…”
Section: Inferiority Complexmentioning
confidence: 99%